2022
DOI: 10.1371/journal.pone.0273907
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with modern contraceptive use among men in Pakistan: Evidence from Pakistan demographic and health survey 2017-18

Abstract: Objective The role of men in family planning is critical in patriarchal societies like Pakistan. The objective of this study is to explore the predictors of modern contraceptive use among Pakistani men. Methods This study is a secondary analysis of Pakistan demographic and health survey (PDHS) 2017–18 data. The study sample consists of 3691 ever married men aged 15–49 years. Pearson’s chi square test and logistic regression were used to find out the determinants of modern contraceptive use among men. Data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Married couples may have varying intentions and desires about family size; a lack of alignment between partners may lead to unintended pregnancies and affect uptake and use of contraception. The uptake of contraceptives among couples is affected by various factors, which include socioeconomic status, education, religion and wrong perceptions about family planning determine the utilization of modern contraception among Pakistani women [ 17 ]. An analysis of the PDHS 2017–18 also established that the perception that contraception is women’s business and discussion of family planning with health workers were significant predictors of modern contraceptive usage in Pakistani men [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Married couples may have varying intentions and desires about family size; a lack of alignment between partners may lead to unintended pregnancies and affect uptake and use of contraception. The uptake of contraceptives among couples is affected by various factors, which include socioeconomic status, education, religion and wrong perceptions about family planning determine the utilization of modern contraception among Pakistani women [ 17 ]. An analysis of the PDHS 2017–18 also established that the perception that contraception is women’s business and discussion of family planning with health workers were significant predictors of modern contraceptive usage in Pakistani men [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as educational level, socioeconomic status, fertility preferences, and the belief that contraception as a woman's responsibility are some predictors of modern contraceptive use among men. Engaging men in discussions about family planning with healthcare providers has shown to have an impact on their contraceptive use, as reported in other studies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 52%
“…The type of contraception used varies according to the age of women [ 5 ]. It has been reported that in sub-Sharan African short-acting contraceptives are commonly used among women who want to limit childbearing, as well as older and married women; compared with long-acting reversible contraceptive (LARC) methods which have long duration of protection and low failure rate [ 6 – 10 , 11 ]. The use of traditional contraceptive methods (TCMs) among older women could be due to a low perceived risk of pregnancy, as well as unstable relationships [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its limitations, the review was able to pinpoint and compile a wide range of contributing factors, barriers, and links that are related to mothers' underuse of health care in Pakistan. The studies provide the most recent information that is currently accessible in terms of time, giving important insight into contemporary practice 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This research is particularly instructive to empowerment studies because previous research in Pakistan found a positive relationship between educational attainment and maternal healthcare use in particular, with Pakistani women who lived in areas with high levels of secondary education being 74% more likely to give birth in a health facility than Pakistani women who lived in areas with lower levels of community education attainment 14 . Moreover, cultural restrictions on male-female relations are linked to maternal mortality; women who encounter issues during labour and delivery might not be able to seek medical help unless a male family member is present 15 .…”
Section: Introductionmentioning
confidence: 99%